HUBUNGAN SELF COMPASSION DENGAN PATUH MINUM OBA PADA PENDERITA HIPERTENSI - Leoma Janice Saragih; Lina Berliana Togatorop (Nursing Current: Jurnal Keperawatan, 2025)
Hypertension is a chronic condition that requires consistent medication adherence to prevent serious complications. However, many hypertension sufferers experience difficulty taking medication regularly as advised. Although medication adherence is critical in hypertension, little is known about the role of self-compassion. This study aims to analyze the relationship between self-compassion and medication adherence in hypertension patients undergoing treatment at a Health Center in Jakarta. A quantitative, cross-sectional design was employed, and data were analyzed using the chi-square test. A total of 100 respondents were selected through purposive sampling. The instruments used were the Self-Compassion Scale (SCS) and the Morisky Medication Adherence Scale-8 (MMAS-8). The results showed a significant relationship between self-compassion and medication adherence in hypertension patients (p-value < 0.001). Although 61% of participants demonstrated high self-compassion, only 39.3% reported high medication adherence. These findings suggest the importance of incorporating psychological components, such as self-compassion, into educational and behavioral interventions to improve treatment adherence and reduce the risk of hypertension-related complications.